(untitled) (Bangladesh Journal of Botany, 2020)
Results of a pot experiment carried out on spinach with vermicompost (5, 10 and 15 ton/ha), phospho-rous (10, 20 and 30 kg/ha) and potassium (20, 30 and 40 kg/ha) fertilizers showed that plant height, leaf area, fresh and dry weight of plants increased significantly (p ≤ 0.5) over the control. Highest height (23.55 cm), leaf area (80.88 cm2/plant), fresh weight (3.838 g/plant) and dry weight (0.274 g/plant) were maximum in VC15P20K30, VC15P30K30, VC10P20K30 and VC10P10K40, respectively, while leaf number was almost same in all the plants. Highest protein content (24.61%) was obtained in the treatment VC15P10K20. Highest dry matter of leaf was obtained at VC10P10K40, but the highest protein content was at VC15P10K20 which might be due to dilution effect. Similar values of protein content were obtained in treatments VC5P20K30, VC5P20K40, VC5P30K20, VC15P10K40, VC15P20K30 and VC15P30K20. Maximum value of nitrogen, phosphorous (1.621%) and potassium (4.066%) were obtained in treatments VC5P20K20 and VC10 P30 K40, VC15 P10 K20, respectively.